Triangulasi dan Analisis Domain; Meningkatkan Kredibilitas dan Kedalaman Penelitian Kualitatif - Malik, Rahman; Susanti, Rina; Hidir, Achmad; Resdati; Ihsan, Muhammad; Dzulqarnain, Muhammad Faizal (KAMBOTI: Jurnal Sosial dan Humaniora, 2025)
This study explores the synergistic relationship between triangulation and domain analysis and how their integration can improve the overall quality of qualitative research. Triangulation enhances trustworthiness by validating findings through comparisons of data collected from multiple sources, methods, or investigators. Meanwhile, domain analysis, rooted in ethnographic semantics, offers a systematic way to uncover the meaning and structure embedded in the validated data. When applied together, these two approaches enable researchers to generate findings that are both credible and rich in interpretation. Triangulation addresses issues of reliability and bias, ensuring that conclusions are supported by diverse evidence. Domain analysis then deepens understanding by identifying semantic relationships and constructing relevant cultural or conceptual domains directly from participants’ perspectives. This study employs a Narrative Literature Review method to synthesize theoretical and methodological insights, building a conceptual link between methodological rigor and interpretative depth. The results are expected to provide guidance for researchers in improving credibility, dependability, and confirmability in qualitative research. Overall, integrating triangulation and domain analysis offers a strong foundation for producing meaningful and trustworthy interpretations, thereby contributing to both methodological strengthening and theoretical development in qualitative inquiry.